If it's not what You are looking for type in the equation solver your own equation and let us solve it.
a+7/3=-3
We move all terms to the left:
a+7/3-(-3)=0
We add all the numbers together, and all the variables
a+3+7/3=0
We multiply all the terms by the denominator
a*3+7+3*3=0
We add all the numbers together, and all the variables
a*3+16=0
Wy multiply elements
3a+16=0
We move all terms containing a to the left, all other terms to the right
3a=-16
a=-16/3
a=-5+1/3
| −6x−16=2x | | 8h=8+10h | | 28+21m-14=35+14-14m | | 7x-2+1=5x+7 | | 3x+2=-x+34 | | 7(2n-3)=119 | | 28+21m-14=35+14-24m | | -5(9+y)=20-3+6y | | (3x)=(2x)+65 | | -4+4x=90 | | (2x-12)+(3x-15)=180 | | 4p-2=26 | | 3x+9=9x+43 | | -3=a+15 | | (2x+10)=46= | | 4(g+8)=7-+4g | | -(4x-4)=24 | | 6x-2+6x=-74 | | 6.35x+9=40.3225+3x | | 9+8p=-3p | | 10=15c | | 53=3b-1 | | -5x+10+4x=17 | | 4.29x-0.692=11.749 | | -(1-n)=3(2n-2) | | 6k+15=27 | | 3k+15=2k-12 | | 7(4x+8)=2(14+14x)+28 | | -8+2x+2x=-16 | | 2)198=-4x+2(-6x+3) | | 6c+3=30 | | x-3/12=x/5 |